History and Literature in the Historical Novels of Ksaver Šandor Gjalski - Coha, Suzana (Poznańskie Studia Slawistyczne, 2023)
The paper begins by asserting that the historical novels of Ksaver Šandor Gjalski have received special treatment in Croatian literary historiography, which tends to ascribe to them a more a documentary and historiographic rather than literary value. This paper will analyse the Romantic, realist and modernist features of Gjalski’s historical novels Osvit. Slike iz tridesetih godina (Dawn. Pictures from the [18]30s) (1892) and Za materinsku riječ. Slike iz četrdeset osme godine (For the Maternal Word. Pictures from [18]48) (1906). In the light of theories of histories as stories (narratives), this paper will indicate that their so-called documentary value is attributable to literary strategies that are used to interpret the past they represent in a specific way, and not to record what is assumed to be the authentic past.